Studi Proses Penerimaan Awak Kapal di PT Berlian Laju Tanker - Lintang Sahara, Andini; Yozar Firdaus Amrullah; Dian Kurnianingsari; Suryandari, Upik (Politeknik Ilmu Pelayaran Semarang, 2025)
The success of ship operations largely depends on the availability of competent crew members. Recruitment is a crucial stage to ensure the fulfillment of competency standards in accordance with regulations and industry needs. However, challenges such as limited human resources, regulatory changes, and global competition often hinder its effectiveness. PT Berlian Laju Tanker, as a national shipping company, faces similar conditions, making it necessary to analyze the recruitment system it implements. This study uses a qualitative descriptive method aimed at providing an in-depth description of the crew recruitment process at PT Berlian Laju Tanker. Data collection techniques include direct observation of recruitment activities, structured interviews with related parties such as the Crewing Manager, Crew Development, and Chief Officer, as well as documentation from the company. To ensure data validity, source and method triangulation techniques were applied to confirm that the data obtained are valid and reliable. The analysis was conducted through data reduction, data presentation, and inductive conclusion drawing to gain a comprehensive understanding of the recruitment challenges and strategies implemented by the company. The results show that the recruitment process at PT Berlian Laju Tanker consists of several stages, including administrative selection, computer-based testing (CBT), final interviews, and medical check-ups, all coordinated by the Crew Management and Manning division. However, several obstacles remain, such as a limited standby crew database, time-consuming manual processes, and a lack of interdepartmental coordination. To address these issues, the company has begun developing a digital recruitment system and establishing partnerships with maritime education institutions to improve the speed, efficiency, and quality of recruited personnel.